A new method for data filtering in RFID middleware. (1st January 2011) - Vahdati, Farahnaz; Javidan, Reza; Faraahi, Ahmad
With rapidly increasing development of RFID (radio frequency identification) applications, the RFID middleware has become a very hot topic. RFID middleware is a new breed of application software which facilitates data communication between automatic identification equipments (such as RFID readers) and enterprise applications. RFID data, however, contain false readings and duplicates. Such data cannot be used directly by applications unless they are filtered and cleaned. To compensate for the inherent unreliability of RFID data streams, most RFID middleware systems employ a 'smoothing filter'. In this paper, a new smoothing filter approach is proposed which is based on the concept of processing the status of tag's readings. The proposed method uses some rules for solving false positives and false negatives to provide accurate RFID data for applications. The simulation results on prototype data show the effectiveness of the proposed method.